PERSEPSI GURU PAMONG TERHADAP MAHASISWA PL DALAM MENGGUNAKAN MEDIA PEMBELAJARAN IPS DI SMP NEGERI 31 PADANG - YANI, FITRI - (Pendidikan Sejarah, 2014)
The background of this study is the fact that collage students have to be able to use the appropriate learning strategy to be applied in explaining the certain material.This is caused by the fact there is not best strategy, media, or method to all subjects materials. The speech method that is used for students is assumed from many difficult factors include to collage students outlook or understanding about many methods that is assumed it is still minim and the limit of facility and access in school to use strategy, media, or other methods. Meanwhile, this study intends to describe Guardian Teachers Perception Towards Practician Teacher In Using Social Knowledge Learning Media In SMPN 31 Padang. Result of this study is : Guardian Teachers Perception Towards PPLK collage students in managing the learning process, they are not able yet to use learning media well. It is caused by the collage students less understanding toward the media function, then the collage students incability in selecting appropriate media to explain the certain material of the subject, also the time limitation to use media in explaining the certain material of the subject.